2018
DOI: 10.1029/2017jb015409
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Anisotropy of the Upper Mantle Below the Western Rift, East Africa

Abstract: Although the East African rift system formed in cratonic lithosphere above a large‐scale mantle upwelling, some sectors have voluminous magmatism, while others have isolated, small‐volume eruptive centers. We conduct teleseismic shear wave splitting analyses on data from 5 lake‐bottom seismometers and 67 land stations in the Tanganyika‐Rukwa‐Malawi rift zone, including the Rungwe Volcanic Province (RVP), and from 5 seismometers in the Kivu rift and Virunga Volcanic Province, to evaluate rift‐perpendicular stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 90 publications
2
32
0
Order By: Relevance
“…Although spatial gaps remain in our knowledge of the Western rift, the lowest P and S wave velocity regions underlie isolated volcanic provinces (e.g., Accardo et al, ; Mulibo & Nyblade, ; O'Donnell et al, ). Mantle anisotropy patterns determined from SKS‐splitting measurements for the Tanganyika‐Rukwa‐Malawi rift region are consistent with asthenospheric flow around cratonic roots, possibly enhanced by oriented melt pockets beneath the Rungwe Volcanic Province (Tepp et al, ).…”
Section: Tectonics Of the Tanganyika‐rukwa Rift Zonementioning
confidence: 72%
See 1 more Smart Citation
“…Although spatial gaps remain in our knowledge of the Western rift, the lowest P and S wave velocity regions underlie isolated volcanic provinces (e.g., Accardo et al, ; Mulibo & Nyblade, ; O'Donnell et al, ). Mantle anisotropy patterns determined from SKS‐splitting measurements for the Tanganyika‐Rukwa‐Malawi rift region are consistent with asthenospheric flow around cratonic roots, possibly enhanced by oriented melt pockets beneath the Rungwe Volcanic Province (Tepp et al, ).…”
Section: Tectonics Of the Tanganyika‐rukwa Rift Zonementioning
confidence: 72%
“…Map of the study area (after Hodgson et al, ; Tepp et al, ) with major basins, border faults, and major faults in the S. Tanganyika‐Rukwa rift zone (after Delvaux et al, ; Ebinger, ; Kervyn et al, ; Morley, ). Purple inverted triangles are the array used in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Many (~60%) of the stations used in this study are located in the East African Rift. Previous shear‐wave splitting studies in this region (Homuth et al, ; Gao et al, ; Bagley & Nyblade, ; Tepp et al, ) have shown that apparent splitting varies strongly both spatially and with backazimuth. This leads to the conclusion that anisotropy in the upper mantle beneath the East African Rift is highly complex, with strong lateral variation and multiple layers of anisotropy.…”
Section: Interpretation Of Splitting Discrepanciesmentioning
confidence: 82%
“…Earthquake distributions, magnitudes, and source mechanisms from the seismically and volcanically active Malawi rift and Miocene‐Recent Rungwe Volcanic Province (RVP), Africa, provide critical constraints on fault kinematics and crustal rheology during rifting of cratonic lithosphere. Extensive crust and mantle imaging in this area has been undertaken as part of the Study of Extension and maGmatism in Malawi aNd Tanzania (SEGMeNT) project and reanalyses of earlier data (Accardo et al, ; Borrego et al, ; Grijalva et al, ; McCartney & Scholz, ; Tepp et al, ). The SEGMeNT study area includes the site of a 2‐week‐long sequence of nine Mw 4.9‐6.0 earthquakes in 2009 (Biggs et al, ; Gaherty et al, ; Kolawole et al, , ), and a 2014 Mw 5.2 earthquake recorded by the SEGMeNT array.…”
Section: Introductionmentioning
confidence: 99%